Plasma Procarboxypeptidase U in Men with Symptomatic Coronary Artery Disease - Silveira, Angela; Schatteman, Katinka; Goossens, Filip; Moor, Elisabeth; Scharpé, Simon; Strömqvist, Mats; Hendriks, Dirk; Hamsten, Anders (Thrombosis and Haemostasis, 2000)
Procarboxypeptidase U (proCPU) is the plasma precursor of carboxypeptidase U (CPU, carboxypeptidase R, plasma carboxypeptidase B or activated thrombin-activatable fibrinolysis inhibitor, TAFIa). CPU removes C-terminal lysine residues that act as plasminogen binding sites from partially degraded fibrin, thereby down-regulating plasminogen activation and fibrinolysis. The present study was carried out as a pilot study to examine whether the plasma proCPU concentration is related to the presence of coronary artery disease (CAD) and/or to levels of established risk indicators for CAD, in a case-control study of 110 men requiring coronary artery bypass grafting (CABG) because of stable angina pectoris. The preoperative plasma proCPU level in the CABG patients was significantly higher than in population-based controls (1029 ± 154 vs. 974 ± 140 U/L, p <0.05). In addition, in a subset of the patients (n = 31) the proCPU concentration, which was significantly lower on the third postoperative day (−17 ± 10%), had increased significantly on the sixth day (+14 ± 12%) after surgery, compared with the preoperative level. In both patients and controls, proCPU concentration was strongly and positively associated with factor VII amidolytic activity and protein C activity, suggesting a common mechanism modulating the plasma levels of these proteins. Otherwise, statistically significant correlations with proCPU were group-specific. In the patients, proCPU correlated significantly with plasma fibrinogen and protein S. In the controls, proCPU correlated significantly with concentrations of cholesterol in plasma, VLDL and LDL. In addition, proCPU correlated significantly with C-reactive protein and haptoglobin levels in the controls only, indicating that also inflammatory mechanisms are involved in the regulation of plasma proCPU. These results suggest that a mechanism exists by which fibrinolytic function is impaired in a manner that is likely to result in more stable fibrin deposits and increase the risk of precocious CAD as well as early occlusion of venous bypass grafts.
Keywords: Procarboxypeptidase U; TAFI; coronary artery disease; bypass surgery; fibrinolysis